ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI PROGRESSIVE MUSCLE RELAXATION UNTUK MENGURANGI MASALAH KECEMASAN PADA IBU PRIMIGRAVIDA YANG DI RUJUK KE RS BHAYANGKARA TK.I R. SAID SUKANTO - Vernanda Erlita Vebyana, (2023)
Pregnancy is the meeting of ovum cells with sperm cells that grow and develop into a fetus in the uterus for approximately 37 weeks to 42 weeks. Primigravida is a woman who is experiencing pregnancy for the first time. Where in primigravida mothers still have little knowledge and experience, so mothers are more easily afraid and anxious. Anxiety is a feeling of excessive worry that can cause emotional, cognitive, behavioral and physical symptoms. One method that can be used to reduce anxiety is progressive muscle relaxation therapy. Progressive muscle relaxation therapy is a relaxation therapy that is performed by tightening and relaxing the muscles in certain parts of the body sequentially at one time which creates a feeling of physical relaxation. Measuring the level of anxiety itself was carried out using the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The results of this study were that in managed patients the anxiety score was from 23 to 5. Meanwhile, in patients who resumed the anxiety score decreased from 28 to 8. Conclusion: with the same intervention and duration, the anxiety scores in both patients equally decreased and this proves that therapy progressive muscle relaxation can reduce the anxiety score experienced by primigravida pregnant women who are referred to health care centers. Keywords : anxiety, primigravida, progressive muscle relaxation